Streptococcus intermedius: An Unusual Case of Purulent Pericarditis - Kara J. Denby; Ryan D. Byrne; Oscar G. Gómez-Duarte (Case Reports in Infectious Diseases)
Purulent pericarditis is a rare diagnosis with life-threatening implications due to the rapid accumulation of pericardial material, swiftly progressing to tamponade physiology. The nature of its quickly evolving and severe implications demands a low threshold for diagnostic consideration where appropriate. We present an unusual case of purulent pericarditis secondary to Streptococcus intermedius in a previously healthy male adolescent without traditional risk factors, which raises the question of whether emergent S. intermedius species may have acquired novel molecular mechanisms.